A new sight into the glass forming ability caused by doping on Ba- and Ti-site in BaTi2O5 glass. (1st October 2020) - Liu, Hao; Ge, Xuan; Hu, Qiaodan; Yang, Fan; Li, Jianguo
Abstract: La- and Nb-doped BaTi2 O5 (BT2 ) spherical glasses were prepared by a containerless aerodynamic levitation method and their glass-forming regions were established. It is found that La-doping on the Ba-site (network-modifier) and Nb-doping on the Ti-site (network-former) show distinct difference in the glass-forming region: less than 10 % La can replace Ba whereas 40 % Nb can incorporate into BT2 glass. The distinction in glass-forming ability induced by La- and Nb-doping is discussed mainly from the structural arrangement of the glass. Raman spectroscopy analysis shows that La-doping elongates the short Ti–O bonds in the distorted [TiO5 ] polyhedra and thus relaxes the network. Nb-doping introduces [NbO6 ] polyhedra into BT2 and there exists a critical doping level (20 %), below which incorporation of Nb into BT2 relaxes the [TiO n ] polyhedra by shortening the long Ti–O bond and above which [NbO6 ] starts to participate in the network skeleton construction resulting in a dramatic change in the glass structure, which is supported by the dramatic change in the exothermic peak on the DTA curves. This work triggers the speculation that the network-modifiers in BT2 glass possess a very important role in the structure of network-former skeleton than those in glasses based on traditional network-former oxides such as SiO2, GeO2 and B2 O3, which may provide a useful strategy for modifying the properties of these novel glasses by chemical doping.